2015
DOI: 10.1530/eje-14-0818
|View full text |Cite
|
Sign up to set email alerts
|

RET Cys634Arg mutation confers a more aggressive multiple endocrine neoplasia type 2A phenotype than Cys634Tyr mutation

Abstract: Objective: Specific germline mutations in the RET proto-oncogene are correlated with clinical features in multiple endocrine neoplasia type 2A (MEN2A); however, data are scarce regarding differences in clinical profiles dependent on the type of nucleotide and amino acid substitution at the same codon. We aimed to analyse differences in clinical risk profiles and outcomes among different amino acids encoded by codon 634. Design: The study was retrospective and multicentric. Methods: We collected data included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 25 publications
(44 reference statements)
6
25
2
Order By: Relevance
“…Here we demonstrated that different amino acid substitutions in RET codon 634 were associated with significant differences in phaeo penetrance ( P <.0045, log‐rank test), with the highest penetrance in Cys634Arg substitution, followed by Cys634Tyr, Cys634Trp, Cys634Gly, and Cys634Phe (Figure ). These results are in agreement with findings from Japanese and Spanish studies. The Cys634Arg mutation is also associated with higher penetrance of MTC and primary hyperparathyroidism compared to other amino acid substitutions .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here we demonstrated that different amino acid substitutions in RET codon 634 were associated with significant differences in phaeo penetrance ( P <.0045, log‐rank test), with the highest penetrance in Cys634Arg substitution, followed by Cys634Tyr, Cys634Trp, Cys634Gly, and Cys634Phe (Figure ). These results are in agreement with findings from Japanese and Spanish studies. The Cys634Arg mutation is also associated with higher penetrance of MTC and primary hyperparathyroidism compared to other amino acid substitutions .…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with findings from Japanese and Spanish studies. The Cys634Arg mutation is also associated with higher penetrance of MTC and primary hyperparathyroidism compared to other amino acid substitutions . Different amino acid substitutions in codon 634 may alter the biochemistry of the RET receptor in the extracellular location, potentially inducing a variable degree of ligand‐independent protein dimerization.…”
Section: Discussionsupporting
confidence: 91%
“…8 A recent Spanish Online National Database study linked substitution by arginine in cysteine codon 634 to higher penetrance of MTC, phaeochromocytoma and hyperparathyroidism than substitution by tyrosine. 9 In other series, substitution of cysteine with or without arginine had no effect on the age of thyroidectomy, 10,11 but was associated more often with metastatic involvement. 11 In previous publications, correction for multiple testing, if performed at all, was not employed consistently so that some of the findings presented actually may have been spurious (falsepositive).…”
Section: Introductionmentioning
confidence: 91%
“…The latter finding of greater penetrance of primary hyperparathyroidism among C634R carriers ( vs all other codon 634 carriers) was confirmed by another research group . A recent Spanish Online National Database study linked substitution by arginine in cysteine codon 634 to higher penetrance of MTC, phaeochromocytoma and hyperparathyroidism than substitution by tyrosine . In other series, substitution of cysteine with or without arginine had no effect on the age of thyroidectomy, but was associated more often with metastatic involvement …”
Section: Introductionmentioning
confidence: 99%
“…Often, tumours show mutational heterogeneity, that is, RET mutations may be found in subpopulations of tumour cells rather than the entire tumour [70,71] . Different amino acid substitutions at a particular RET codon may be associated with phenotypes with different tumour aggressiveness [72] . An important limitation of genomic analysis is epigenetic influences.…”
Section: Contribution Of Geneticsmentioning
confidence: 99%